Perancangan Sistem Informasi Laporan Payment Nasabah Perusahaan Pinjaman Online Berbasis Web Dengan Menggunakan Metode Rapid Aplication Development (RAD) - Pilda Ulan Sari; Angga Suryadi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
PT Easy Calleg Teknologi is one of the online loan companies that still implements its reporting system in a conventional system, this manual report pattern is centered on the leader who provides customer payment data every day. Because the concept of this report really takes a long time and also requires accuracy, especially in inputting reports and having to calculate the results of all customers who pay bills. To resolve the issue. The author uses the Rapid Application Development model in making reports. It is hoped that by using the Rapid Application Development model, employees can make reports systematically and quickly. So that by implementing the Rapid Application Development model, it can help and facilitate employees in making reports. In this implementation, the application uses the PHP programming language and stores the data using MySQL. Based on the analysis results of the Rapid Application Development model, it can be concluded that the reporting process becomes more effective and faster, thus making employees quickly make reports. Researchers have also provided a web-based application program to make it easier to systematically make daily, weekly and monthly reports.